Protection From Influenza by Intramuscular Gene Vector Delivery of a Broadly Neutralizing Nanobody Does Not Depend on Antibody Dependent Cellular Cytotoxicity - Del Rosario, Joanne Marie M.; Smith, Matthew; Zaki, Kam; Risley, Paul; Temperton, Nigel; Engelhardt, Othmar G.; Collins, Mary; Takeuchi, Yasuhiro; Hufton, Simon E. (Frontiers in Immunology, 2020)
Cross-subtype neutralizing single domain antibodies against influenza present new opportunities for immunoprophylaxis and pandemic preparedness. Their simple modular structure and single open reading frame format are highly amenable to gene therapy-mediated delivery. We have previously described R1a-B6, an alpaca-derived single domain antibody (nanobody), that is capable of potent cross-subtype neutralization in vitro of H1N1, H5N1, H2N2, and H9N2 influenza viruses, through binding to a highly conserved epitope in the influenza hemagglutinin stem region. To evaluate the potential of R1a-B6 for immunoprophylaxis, we have reformatted it as an Fc fusion for adeno-associated viral (AAV) vector delivery. Our findings demonstrate that a single intramuscular injection in mice of AAV encoding R1a-B6 fused to Fc fragments of different isotypes equipped either, with or without, ADCC activity was able to drive sustained high-level expression (0.5 - 1.1 mg/mL) in sera with no evidence of reduction for up to 6 months. R1a-B6-Fc fusions of both isotypes gave complete protection against lethal challenge with both pandemic A/California/07/2009 (H1N1)pdm09 and avian influenza A/Vietnam/1194/2004 (H5N1). This data suggests that R1a-B6 is capable of cross-subtype protection and antibody dependent cellular cytotoxicity (ADCC) was not essential for R1a-B6 efficacy. Our findings demonstrate AAV delivery of cross-subtype neutralizing nanobodies may be an effective strategy to prevent influenza infection and provide long-term protection independent of a host induced immune response.